N'-(5-Fluoro-2-oxo-2,3-dihydro-1H-indol-3-ylidene)benzenesulfonohydrazide - Ali, Hapipah Mohd; Laila, M.; Rizal, Mohd Razali; Ng, Seik Weng (International Union of Crystallography, 2008)
The molecule of the title compound, C14H10FN3O3S, consists of an indole unit and a phenylsulfonyl unit that are disposed in an approximately trans orientation relative to the N-N single bond. Two molecules are arranged about a center of inversion, forming a hydrazide-carbonyl N-H center dot center dot center dot O hydrogen-bonded dimer; the dimers are linked by an indole-sulfonyl N-H center dot center dot center dot O hydrogen bond into a ribbon.